1 Corinthians A Commentary on the First Epistle to the Corinthians - Conzelmann, Hans (Philadelphia Fortress Press, 1975)
Explicates and comments on each verse in an historical and theological context and provides extensive notes on the translation from the Greek text.
Keywords: Bible. -- Corinthians, 1st -- Commentaries. Bible. -- Corinthians, 1st. Bible. -- New Testament. -- Corinthiens, 1re -- Commentaires